The brain prioritizes the basic level of object category abstraction - Michelle R. Greene; Alyssa Magill Rohan (Scientific Reports)
Abstract The same object can be described at multiple levels of abstraction (“parka”, “coat”, “clothing”), yet human observers consistently name objects at a mid-level of specificity known as the basic level. Little is known about the temporal dynamics involved in retrieving neural representations that prioritize the basic level, nor how these dynamics change with evolving task demands. In this study, observers viewed 1080 objects arranged in a three-tier category taxonomy while 64-channel EEG was recorded. Observers performed a categorical one-back task in different recording sessions on the basic or subordinate levels. We used time-resolved multiple regression to assess the utility of superordinate-, basic-, and subordinate-level categories across the scalp. We found robust use of basic-level category information starting at about 50 ms after stimulus onset and moving from posterior electrodes (149 ms) through lateral (261 ms) to anterior sites (332 ms). Task differences were not evident in the first 200 ms of processing but were observed between 200–300 ms after stimulus presentation. Together, this work demonstrates that the object category representations prioritize the basic level and do so relatively early, congruent with results that show that basic-level categorization is an automatic and obligatory process.